Connecting with the subject of our science: Course-of-experience research supports valid theory building in cognitive science - McGann, Marek (Adaptive behavior, 2023)
This commentary addresses the course-of-experience method in the context of calls for improved theorising in psychological science, and in particular the prospect of applying distinctive means of analysis to examine patterns and variance both between people and across contexts. Psychology can benefit by the development of both theories of principle (formal accounts of the structure of phenomena) and constructive theories (formal accounts of the mechanics of phenomena). The course-of-experience method can provide a useful step toward the development of both. Resonances with other work grounded in naturalistic observation identify potential questions that remain as to how the course-of-experience method can address questions about the relationship between individual and collective aspects of experience, but the technique represents a significant boon to the future development of valid cognitive science.